Revitalizing Religious Moderation In The Implementation of Amar Ma’ruf Nahi Munkar at Gentur Islamic Boarding School, Cianjur - Endan HamdanRidwan (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
Religious moderation has been formally established as a national policy by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI) through its incorporation into the 2020–2024 National Medium-Term Development Plan (RPJM), emphasizing the principles of wasathiyah (moderation), justice, and sustainability. This study investigates the implementation of religious moderation education in pesantren institutions as a critical platform for cultivating moral values and behaviors aligned with Islamic teachings and other officially recognized religions in Indonesia. The research aims to revitalize the passive state of religious moderation education among santri, promoting a productive, constructive, tolerant, and patriotic lifestyle. A qualitative documentation method was employed to analyze the implementation process and its outcomes. The findings reveal that Darul Falah Gentur Cianjur Islamic Boarding School has successfully institutionalized religious moderation, in accordance with the Ministry’s 2020-2024 strategic mandate, fostering a legally compliant, tolerant, and moderate religious environment. The originality of this study lies in its empirical evidence demonstrating the effective revitalization of religious moderation practices in traditional pesantren settings, which have often been overlooked in previous research. The study's implications suggest that embedding religious moderation values within the daily lives of santri can strengthen social cohesion, nurture interfaith harmony, and reinforce national unity both within and beyond pesantren communities